Culturally Responsive Teaching (CRT): Effects on Students’ Academic Performance and Science Process Skills in Chemistry - Lovido, Jessa A.; Salazar, Douglas A. (International Journal of Research in Interdisciplinary Studies, 2026)
This study examined the effects of Culturally Responsive Teaching (CRT) on Grade 10 students’ academic performance and science process skills in Chemistry at Kalipay National High School, Gingoog City. CRT emphasizes instruction that connects classroom content to students’ cultural backgrounds, lived experiences, and community contexts. Two intact classes (n=74) participated using a quasi-experimental pretest–posttest design: the experimental group received CRT-based laboratory instruction, while the comparison group received non-CRT lecture-based instruction. Academic achievement was measured using a researcher-developed 61-item test, and science process skills were assessed through Arnold et al.’s (2009) validated instrument. Findings show that the experimental group demonstrated substantially higher academic performance (M=83.06) compared to the non-CRT group (M=41.08), with ANCOVA indicating significant differences (p<.05). Students exposed to CRT also attained higher ratings in science process skills (M=3.36), compared to those under non-CRT instruction (M=2.72), with t-test analysis confirming significant differences across most indicators (p<.05). These results support research suggesting that CRT fosters inclusiveness, inquiry, critical thinking, and conceptual understanding by contextualizing science learning and connecting content to cultural knowledge. The study concludes that CRT effectively enhances science learning outcomes and inquiry competence, particularly in diverse classrooms. Recommendations include integrating CRT into science pedagogy, curriculum design, and teacher training.